Bortezomib, thalidomide, dexamethasone, and panobinostat for patients with relapsed multiple myeloma (MUK-six): a multicentre, open-label, phase 1/2 trial. Issue 12 (December 2016) - Popat, Rakesh; Brown, Sarah R; Flanagan, Louise; Hall, Andrew; Gregory, Walter; Kishore, Bhuvan; Streetly, Matthew; Oakervee, Heather; Yong, Kwee; Cook, Gordon; Low, Eric; Cavenagh, Jamie; et al.
Summary: Background: Panobinostat (a pan histone deacetylase inhibitor) is approved in combination with bortezomib and dexamethasone for patients with relapsed multiple myeloma who have received two or more previous lines of therapy. We aimed to improve the safety of this combination and investigate efficacy by incorporating low-dose thalidomide, using sub-cutaneous weekly bortezomib, and determining the maximum tolerated dose of panobinostat in this regimen. Methods: We did a phase 1/2, multicentre, open-label trial (MUK six) at four hospitals in the UK, enrolling patients with relapsed, or relapsed and refractory, multiple myeloma aged at least 18 years, with an Eastern Cooperative Oncology Group performance status of 2 or less who had previously received 1–4 lines of therapy. Exclusion criteria included any antimyeloma treatment within 28 days of study drugs (except dexamethasone 160 mg >48 h before treatment). We used a rolling six escalation design to determine the maximum tolerated dose of panobinostat, and allocated patients to receive subcutaneous bortezomib 1·3 mg/m 2, and oral thalidomide 100 mg, dexamethasone 20 mg, and panobinostat 10, 15, or 20 mg (escalated to 20 mg according to the escalation schedule). Treatment was given during a 21-day cycle (bortezomib on days 1 and 8; thalidomide every day; dexamethasone on days 1, 2, 8, and 9; and panobinostat on days 1, 3, 5, 8, 10, and 12) for 16 cycles in the absence of disease progression or unacceptable toxicity. Patients were permitted to come off study for autologous stem cell transplantation. The primary objective was to determine the maximum tolerated dose and recommended dose of panobinostat, and to estimate the proportion of patients with an overall response that was equal to a partial response or greater within 16 cycles of treatment at the recommended panobinostat dose in the modified intention-to-treat population. We assessed safety in all patients who received a trial drug (ie, bortezomib, thalidomide, dexamethasone, or panobinostat). This trial is registered atClinicalTrials.gov, numberNCT02145715, and with the ISRCTN registry, number ISRCTN59395590 and is closed to recruitment. Findings: Between Jan 31, 2013, and Oct 30, 2014, we enrolled 57 eligible patients who received at least one dose of trial medication or any drug. One dose-limiting toxicity was reported (grade 3 hyponatremia at the 20 mg dose), therefore the maximum tolerated dose was not reached, and 20 mg was deemed to be the recommended dose. 46 patients were treated with panobinostat 20 mg (the intention-to-treat population). 42 patients (91%, 80% CI 83·4–96·2) of 46 achieved the primary endpoint of an overall response that was equal to a partial response or greater. Most adverse events were grade 1–2 with few occurrences of grade 3–4 diarrhoea or fatigue. The most common adverse events of grade 3 or worse in the safety population (n=57) were reduced neutrophil count (15 [26%]), hypophosphatemia (11 [19%]), and decreased platelet count (8 [14%]). 46 serious adverse events were reported in 27 patients; of 14 suspected to be related to the trial medication, seven (50%) were gastrointestinal disorders. Interpretation: Panobinostat 20 mg in combination with bortezomib, thalidomide, and dexamethasone is an efficacious and well tolerated regimen for patients with relapsed multiple myeloma. Funding: Novartis and Myeloma UK.